The Effect of Health Education through Comic Book Media on Knowledge, Attitudes, and Skills of Breast Self-Examination (BSE) among Female Students at SMAN 8 Mataram - Rusmini, Rusmini; Kurnia, Theresia Avila; Sri Puja Warnis W, Gusti Ayu; Syafiatun, Ghina Aulia (Bima Nursing Journal, 2025)
Abstract